GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Micro- and Nanoplastics in the Human Brain: Mechanistic Plausibility, Translational Challenges, and Links to Neurological Disease Trends - Farshid Ghiyamihoor; Azam Asemi Rad; Parya Hassanifar; Raj Kaur; Janvi Hitenkumar Patel; Ian Kim; Asghar Marzban; Mehdi Mehdizadeh; David B. Levin; Saeid Ghavami; Antoniya Toncheva; Samira Benali; et al. (Molecular Neurobiology, 2026)

Predicting the dust storms using three-hybrid metamodels for integrated dust storm management (case study: Khuzestan Province, Iran) - M. Ansari Ghojghar; S. Piri; R. T. Rad; A. Malekian (International Journal of Environmental Science and Technology, 2026)

Enhanced photocatalytic degradation of methylene blue using aluminum and cerium co-doped ZnO nanocomposite - S. Ameen; R. Fatima; A. A. Kadhem; T. Abbas; M. A. Khan; A. Abbas; I. Hussain; N. Bano; Z. Faraji Rad; A. S. S. Bilal (International Journal of Environmental Science and Technology, 2025)
Photocatalysis has emerged as an established and environmentally sustainable approach for degrading biological pollutants into less hazardous substances. In this work, zinc oxide (ZnO) nanorods co-doped with aluminum and cerium were produced via a single-step hydrothermal technique. The aluminum and cerium co-doped zinc oxide (ACZn) nanocomposite was investigated for structural, morphological, optical, and charge transfer kinetics by using X-ray diffraction, Raman spectroscopy, scanning electron microscopy, UV–Vis diffuse reflectance spectroscopy, and photoluminescence spectroscopic techniques. The absorption spectra were perceived to be redshifted as a result of the increased absorption capacity of the ACZn-based photocatalyst due to the addition of Al and Ce. ACZn nanocomposite demonstrated a significantly enhanced photocatalytic efficiency (PE), achieving a 93% degradation of methylene blue (MB) under simulated solar irradiation, compared to CZn (89% PE), AZn (72% PE), and pristine ZnO (76% PE). This 22% improvement of ACZn relative to pristine ZnO was attributed to refined surface characteristics, decreased band gap energy, and enhanced charge separation efficiency, as demonstrated by kinetic analysis and photoluminescence investigations. Additional photocatalytic measurements disclosed several factors affecting the degradation process of methylene blue including photocatalyst dosage and initial dye concentration. Furthermore, the ACZn photocatalyst demonstrated a robust potential for environmental remediation applications by exhibiting superior reusability for multiple cycles without observing a noticeable decrease in photoactivity. Graphical abstract

Subtyping of mouse pancreatic ductal adenocarcinoma (mPDAC) - L. Arps; S. Müller; M. Zukowska; D. Saur; R. Rad; M. Reichert; I. Heid; M. Mayer; N. Wirges; R. Klopfleisch; K. Steiger (Journal of Comparative Pathology, 2025)

Modeling Wildfire Effects on Ecosystem Services in two Disparate California Watersheds and Communities - Ibrahim Busari; Matthew R. Sloggy; Mani Rouhi Rad; Debabrata Sahoo; Stacy A. Drury; Francisco J. Escobedo (Environmental Management, 2025)
Ecosystem services are important for human well-being and for sustaining environmental quality objectives. Growing concern over extreme wildfire events in various watersheds necessitates understanding their impacts on regulating ecosystems services. Past studies have documented how wildfires regulate ecosystem services, but the distributional impacts of such ecosystem services across various human settlements (i.e. communities) remains understudied, despite renewed focus on how they are increasingly at risk from and being impacted by wildfires. We used the Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) model to examine how two wildfires that occurred in California, USA in 2017 impacted water provisioning, soil loss and sediment delivery, carbon sequestration services, and nutrient delivery in two watersheds and their respective communities. Regression analyses were used to determine the differences in the distribution of ecosystem services before and after the fires, and whether these wildfires exacerbated the differences in impacts to ecosystem services across communities in the watershed. We find that a year following the fires, the amount of biomass in forestland, woodland, and chaparral declined in both studied watersheds, while the amount of grassland increased. The model revealed that the changes in vegetation resulted in losing about 200,000 tons of carbon from the Mark West subwatershed and about 160,000 tons of carbon from the southern California watersheds. The expected mean annual water yield for both watersheds increased by 5% and 42%, respectively post-fire. Expected post-fire phosphorus and nitrogen export also increased. Finally, we found evidence of human community-level differences in the distribution of pre-fire ecosystem services but no evidence that post-fire conditions either exacerbated or alleviated these impacts.

Macroalgal deep genomics illuminate multiple paths to aquatic, photosynthetic multicellularity - David R. Nelson; Alexandra Mystikou; Ashish Jaiswal; Cecilia Rad-Menendez; Michael J. Preston; Frederik De Boever; Diana C. El Assal; Sarah Daakour; Michael W. Lomas; Jean-Claude Twizere; David H. Green; William C. Ratcliff; et al. (Molecular Plant, 2024)

Critical View of Overland Flow Estimation in Semi-arid Catchments Under Land Subsidence with Long-term Field Measurements - O. Bakhshi Rad; A. R. Vaezi; R. Khatibi (Water Resources Management, 2024)

Correction to: Changing climate, changing minds? The effects of natural disasters on public perceptions of climate change - Matthew R. Sloggy; Jordan F. Suter; Mani Rouhi Rad; Dale T. Manning; Chris Goemans (Climatic Change, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Changing opinions on a changing climate: the effects of natural disasters on public perceptions of climate change - Matthew R. Sloggy; Jordan F. Suter; Mani Rouhi Rad; Dale T. Manning; Chris Goemans (Climatic Change, 2021)

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

Differential functional traits underlying the contrasting salt tolerance in Lepidium species - R. Hajiboland; S. Bahrami-Rad; N. Zeinalzade; E. Atazadeh; H. Akhani; C. Poschenrieder (Plant and Soil, 2020)

Letter to the editor regarding article, “Role of glycogen synthase kinase following myocardial infarction and ischemia–reperfusion” - S. Ghaderi; N. Alidadiani; N. Dilaver; H. R. Heidari; R. Parvizi; R. Rahbarghazi; J. Soleimani-Rad; B. Baradaran (Apoptosis, 2019)

Development of the male and female gametophyte in Capsicum annuum L. var. California Wonder - H. Ramezani; A. Chehregani Rad; R. Karamian (Plant Biosystems, 2018)

Applicability of CAAT box-derived polymorphism (CBDP) markers for analysis of genetic diversity in durum wheat - A. Etminan; A. Pour-Aboughadareh; R. Mohammadi; A. Noori; A. Ahmadi-Rad (Cereal Research Communications, 2018)

Role of glycogen synthase kinase following myocardial infarction and ischemia–reperfusion - S. Ghaderi; N. Alidadiani; N. Dilaver; H. R. Heidari; R. Parvizi; R. Rahbarghazi; J. Soleimani-Rad; B. Baradaran (Apoptosis, 2017)

Incorporation of Propionibacteria in Fermented Milks as a Probiotic - M. Moslemi; R. Mazaheri Nezhad Fard; S. M. Hosseini; A. Homayouni-Rad; Amir M. Mortazavian (Critical Reviews in Food Science and Nutrition, 2016)

Diversity in the antimicrobial susceptibility patterns of methicillin-resistant Staphylococcus aureus clones - E. Ghaznavi-Rad; V. Neela; M. Nor Shamsudin; H. Ghasemzadeh Moghaddam; M. Tavakol; A. Belkum; M. R. Etemadi; A. F. Andar-Ali (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

mec-associated dru typing in the epidemiological analysis of ST239 MRSA in Malaysia - E. Ghaznavi-Rad; R. V. Goering; M. Nor Shamsudin; P. L. Weng; Z. Sekawi; M. Tavakol; A. Belkum; V. Neela (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Induction of diabetes by Streptozotocin in rats - A. Akbarzadeh; D. Norouzian; M. R. Mehrabi; Sh. Jamshidi; A. Farhangi; A. Allah Verdi; S. M. A. Mofidian; B. Lame Rad (Indian Journal of Clinical Biochemistry, 2007)

Treatment of streptozotocin induced diabetes in male rats by immunoisolated transplantation of islet cells - A. Akbarzadeh; D. Noruzian; Sh. Jamshidi; A. Farhangi; M. R. Mehrabi; B. Lame Rad; M. Mofidian; A. Allahverdi (Indian Journal of Clinical Biochemistry, 2007)

Sm?Nd dating of fluorite from the worldclass Montroc fluorite deposit, southern Massif Central, France - Marguerite Munoz; Wayne R. Premo; Pierre Courjault-Rad (Mineralium Deposita, 2005)

Gas and fluid venting at the Makran accretionary wedge off Pakistan - U. von Rad; U. Berner; G. Delisle; H. Doose-Rolinski; N. Fechner; P. Linke; A. Lückge; H. A. Roeser; R. Schmaljohann; M. Wiedicke; SONNE 122/130 Scientific Parties; M. Block; et al. (Geo-Marine Letters, 2000)

The herpes simplex virus type 1 ribonucleotide reductaseis required for acute retinal disease - C. R. Brandt; P. Imesch; B. Spencer; B. Eliassi-Rad; N. A. Syed; S. Untawale; N. L. Robinson; D. M. Albert (Archives of Virology, 1997)